Kompetenzmanagement 50+ - Empfehlungen für den Mittelstand - Franziska Genschick; Christiane Al Ghanem; Rüdiger Grimm (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2023)
– This publication aims to use a case study to determine the content and framework conditions of age-sensitive competence management and to derive recommendations for action. By applying qualitative methods such as expert interviews and the analysis of secondary sources, several relevant factors could be identified. The results show that there is no single tool for competence development for people over 50. Instead, it is the combination of different learning formats, groups of participants, methods and content that promotes the acquisition of competencies in the second half of the working life. It is recommended to provide mixedage measures to bring the generations together. At the same time, offerings tailored to the learning needs of the 50+ target group can provide specific benefits - for example, age-homogeneous small groups, age-oriented didactics, or content linked to participants' individual interests. In addition, the research found that employee appraisals play an important role in competency management, both for maintaining and developing competencies in the current position and for creating prospects for a job change. The research showed that in addition to the formal process aspects, the framework conditions, including motivation-related aspects, have a significant impact on the successful implementation of competence management for people over 50. It is recommended that the process be anchored at the top level and implemented through bottom-up and top-down planning and provision of operational measures, pilot projects, information and awareness campaigns, and regular reflection and updating. In particular, the study highlights the importance of the active participation of the employee group aged 50 and over, as well as the decisive role of managers. It also recommends that a fundamental shift in corporate culture toward an appreciative attitude toward all age groups and lifelong learning be pursued. The approaches to action in competence management 50+ should address strategic issues in order to promote the employability of older employees. This publication contributes to the concrete design of a competence management concept for employees 50+. The results can be transferred to other private companies.
Keywords: 650; ältere Mitarbeiter; Mittelstand; Experteninterviews; Qualitative Forschung; Altersgruppe 50+; Altersstruktur; Fachkräftemangel; Renteneintritt; demografische Entwicklung; Altersdurchschnitt